The Blessing Of Umkm Will Be “War Takjil” and Become A Symbol Of Tolerance In Ramadan Culture - Samawa Kantari; Febri Ashari; Endar Purnawan (Pascasarjana, Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2023)
This article discusses the blessings of UMKM on the existence of